A formação de professores indígenas em Ciências da Natureza, na região Norte do Brasil : algumas reflexões - Santa Rosa, Silvana Costa (2018)
The training of indigenous teachers in Brazil comes to fill the gap of this professional in Basic Education in indigenous territories. In the Northern Region of Brazil, the initial training of these teachers is currently carried out by nine undergraduate courses; of these, eight courses offer, among others, the qualification in Ciências da Natureza (CN) [Natural Sciences]. This research aims to study the training proposed in the Projetos Pedagógicos de Curso (PPCs) [Pedagogical Course Projects] of the Licenciaturas Interculturais (LI) [Intercultural Bachelor’s degrees] for the training of indigenous teachers in CN in the Northern region of Brazil and the vision of the representatives of the national movement of the Educação Escolar Indígena (EEI) [Indigenous School Education], collaborators of this research, about this formation. The research uses a qualitative approach and the collections were performed through documentary analysis and interviews. In the documentary analysis we studied the PPCs of five LI of the North Region and the guidelines and referential for the training of indigenous teachers. The interviews were conducted with representatives of the Brazilian EEI movement, such as indigenous and non-indigenous intellectuals, indigenous teachers and IEE managers. These training proposals in CN indicate that in the elaboration of the PPCs it was sought to attend the indigenous specificities. Among these proposals we observe proximity between objectives and justifications, as well as in times and spaces. In the methodological and organizational aspects, we verified greater diversity in the proposals regarding the education arrengements, academic regime, curricular organization, activities and methodology. We find that in these PPCs political knowledge has a greater presence in general formation than in specific formation in CN, explaining that in most of these PPCs, about specific formation, there is some distance from the discussions about the social role of Science. Regarding the content knowledge, in two PPCs the contents are centered on the so-called universal knowledge; in others the universal knowledge is articulated with other knowledge, stressing indigenous wisdom. We verified that all training proposals seek to promote dialogue between knowledges, but it was not clear how will this proposal be implemented. On the collaborators point of view, we observe that they think of courses organized according to the aspirations of the indigenous peoples as a way of contributing with their corporate projects, configuring as spaces of struggle, that is, of political formation, with the participation of indigenous leaders and wise men in this formation. In their speeches we can notice the demand that indigenous teachers have a solid formation regarding scientific contents, however, this formation and practice cannot be separated from the dialogue with indigenous tradition. Thus, in comparison to the PPCs, it was spoken in defense of intercultural dialogue. The collaborators also make a critical analysis of the indigenous practices and the scientific contents to be worked on in the teacher training. We concluded that these proposals contemplate many aspects of the official documents and the indigenous movement’s agenda, since they announce a formation based on the specificities of the indigenous peoples. However, regarding the proposal of qualification in CN there is a certain approximation and detachment from the assumptions of intercultural education that were explained in the elements regarding curricular organization, in some projects with a disciplinary character, and the content centered on the so-called universal knowledge.